Will green financial policy influence energy consumption structure? Evidence from pilot zones for green finance reform and innovation in China - Cui, Genghao; Mao, Huizhen; Dong, Xin; Shao, Lin; Wang, Miao (Frontiers in Environmental Science, 2023)
Green finance is considered an effective way to promote economic development and environmental protection. The Chinese government has formulated the green financial reform and innovation policy to change energy consumption structure (ECS) and achieved the goal of economic development and environmental protection. This paper considers the pilot zones for green finance reform and innovation (PZGFRI) set up in 2017 as a quasi-natural experiment, and we adopt the synthetic control method (SCM) to evaluate the possible policy effects of the PZGFRI on the ECS based on panel data from 30 provincial-level administrative regions from 2013 to 2019.The empirical results reveal that the PZGFRI set-up plays a key role in influencing the ECS. The PZGFRI policy significantly optimizes the ECS in both Zhejiang Province and Guizhou Province, with the investigative result in Guizhou Province being better than that in Zhejiang Province. Meanwhile, placebo test and robustness tests are still valid. This study contributes to a better understanding of the effectiveness of China's PZGGRI policy on the ECS, and also is helpful to provide a reference for our country's green finance to promote the adjustment of ECS. .